Money Demand Responsiveness to the Rate of Return on Money: A Methodological Critique - Carlson, John A.; Frew, James R. (Journal of Political Economy, 1980)
This paper challenges the empirical basis for the current belief that competition forces banks to make immediate implicit-interest payments on demand deposits equal to the marginal earnings on those deposits and that this implicit return has a strong effect on the demand for money. Klein's method of defining the implicit return as a function of the money supply and of the return on an alternative asset and then adding that implicit return to a money-demand equation is likely to produce his results whether or not the world behaves as he hypothesizes.